2022
DOI: 10.2147/jir.s369176
|View full text |Cite
|
Sign up to set email alerts
|

Blood Coral Polysaccharide Helps Prevent D-Gal/LPS-Induced Acute Liver Failure in Mice

Abstract: The liver protection of blood coral polysaccharide (BCP) was investigated. Materials and Methods: We evaluated the effect of BCP on liver pathology, liver function, oxidation and inflammation-related indicators of D-Gal/LPS-induced acute liver failure (ALF) mice in vivo. Results: Liver index and liver pathology observation in mice showed that BCP could inhibit liver tissue swelling and hemorrhage, hepatocyte damage, and inflammatory infiltration in ALF. Serum liver function results showed that BCP effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…A relationship between liver damage and oxidative stress has been well established [18]. Experimental models of D-Gal-induced liver damage have provided evidence that the morphological and functional characteristics of human hepatitis are almost identical [19][20][21]. Previous studies have suggested that inflammation is a major cause of liver damage [9,22].…”
Section: Introductionmentioning
confidence: 99%
“…A relationship between liver damage and oxidative stress has been well established [18]. Experimental models of D-Gal-induced liver damage have provided evidence that the morphological and functional characteristics of human hepatitis are almost identical [19][20][21]. Previous studies have suggested that inflammation is a major cause of liver damage [9,22].…”
Section: Introductionmentioning
confidence: 99%